The Impact of Environmental, Social, and Governance (ESG) Performance on Financial Reporting Quality: International Evidence - Şeker, Yasin; Şengür, Evren Dilek (Ekonomika, 2021)
This study investigates the relationship between environmental, social, and governance (ESG) performance and financial reporting quality (FRQ) through the use of data from Datastream, Refinitive Eikon and ASSET4 databases. The initial sample of the study covers all available firms in ASSET4. After eliminating firms with missing data, the final sample of the study consists of 16,072 firm-year observations from 35 countries, covering the years from 2010 to 2017. Several FRQ proxies and firms’ ESG performance indicators are used in the study. The panel regression findings reveal that firms’ ESG performance has a positive impact on FRQ. In other words, it has been found that improving the ESG performance of firms yields higher FRQs. As for ESG pillars, this study finds a positive and statistically significant relationship between FRQ and environmental and governance pillars. The study extends the literature by providing international evidence not only about the aggregate effects of firms’ ESG performance on FRQ but also the effects of each of the three ESG pillars on FRQ.